Analysis of fatigue behaviour of notched specimens made of fibreglass reinforced polyamide by means of a cohesive model. (December 2017) - Casado, J.A.; Gutiérrez-Solana, F.; Carrascal, I.; Diego, S.; Ferreño, D.
Abstract: Fatigue tests until fracture of five notched specimens of short glass fibre reinforced polyamide, with a humidity of 2.5%, were carried out at 23, 28, 33, 38 and 43 °C. A correlation between the environmental temperature and the number of cycles to failure was established. Three different regions of strain were observed, namely, transient, steady-state and pre-failure. Strain and strain-rate during the creep-fatigue process revealed the existence of non-temperature dependent critical strains between these regions. The fractographic study performed after failure suggested the suitability of describing the stress distribution in the remnant ligament through a cohesive model. This is based on the observed fact that, at the crack tip, the matrix and the fibres debond, giving rise to crazing mechanisms so that the ultimate bearing ability of the material relies on the matrix. The calculations involved in the cohesive model were based on the information provided by the fractographic study and the real-time measurements of the crack growth by means of an infrared thermographic camera. Based on this methodology, the cohesive stress of the material was estimated. In a last stage, the surface roughness of the samples was determined after being tested, revealing a reliable correlation between the roughness and the fracture micromechanisms undergone by the underlying material. This correlation makes it possible to use the surface roughness of an in-service component as a parameter to evaluate the level of microstructural damage that it has experienced. Highlights: Fatigue tests of notched specimens, made of short glass fibre reinforced polyamide, between 23 °c and 43 °C. A correlation between temperature and number of cycles to failure was established. Transient, steady-state and pre-failure regions were identified. The stress distribution was modelled through a cohesive model. The surface roughness of the samples was correlated with the fracture micromechanisms undergone by the material.